The Effect Of Training and Work Motivation To Employee Performance PT. Nasmoco Pemuda Semarang - Ashari, Muhammad; Prihatini, Apriatni Endang; Prabawani, Bulan (Jurnal Ilmu Administrasi Bisnis, 2014)
AbstractPT. Nasmoco Pemuda Semarang is a company that focus on sales and service for four wheel vehicles (car) with Toyota as their brand. For 5 years later, the company accomplishment always exceed the targets however in terms of percentage always decrease every years. This caused by lack of employee training PT. Nasmoco Pemuda Semarang. This research aimed to determine the effect training (X1) and work motivation (X2) against employee performance (Y) PT. Nasmoco Pemuda Semarang. Type of this research is explanatory research, with a population that all of employee on service division which amounts to 62 people. The sample used in this research as many as 62 respondents with techniques of sampling using a Proportionate Stratified Random Sampling method (sampling technique based on conditions or certain categories). Data collection in this research using interview and questionnaires. The technique data analysis using validity test, reliability test, simple linear regression, multiple linear regression, t test and F test with the tools SPSS 20.0.            Based on statistic calculation can be known simple linear regression equation between training with employee performance is Y= 8,632 + 0,618 X1. Linear regression equation between motivation with employee performance is Y= 4,581 + 0,775 X2. Based on there equation can be known there is positive influence in partial between each variable X against variable Y. Multiple linear regression is Y= 2,856 + 0,363 X1 + 0,538 X2. This research concludes that training and work motivation have influence to employee performance. Training and motivation explain the employee performance variable by 48,7% where training has influence as 36,5% and motivation has influence as 41,7%. Training and motivation have simultaneously significant effect against employee performance PT. Nasmoco Pemuda Semarang where the motivation has the highest influence.            Suggestion which can be submitted in this research is the company give training continuously with can be invite the practitioners that expert in it, so that employee performance can be better.